Microsystems for bioelectronics : the nanomorphic cell - Zhirnov, Victor V. (Micro and nano technologies series, 2010)
This book considers physical principles and trends in extremely scaled autonomous microsystems for biomedical applications. It provides a physics-based assessment of the ultimate potential of miniaturization technologies. In particular, fundamental scaling limits for energy sources, sensors, computation and communication subsystems are developed. The book is comprised of seven chapters that examine various facets of semiconductor bioelectronic microsystems. The book targets a broad audience with engineering background and can also be useful for the biomedical community. Rapid advances in microfabrication technologies are offering new opportunities and capabilities to develop systems for biomedical applications, such as diagnostics and therapy. There is a need for a comprehensive treatment of integrated microsystems comprised of diverse components. In particular is important to understand the scaling limits both for the system and its components. An additional intent is to promote innovative thinking about integrated microsystems. Discusses the diverse components that make up Microsystems Outlines the problems with miniaturization of energy sources Perfect reference for those in both the Engineering and Medical Profession.